PENGARUH KINERJA LINGKUNGAN DAN PENGUNGKAPAN LINGKUNGAN TERHADAP MANAJEMEN LABA RIIL - Hestina Muzdalipatul Farha (2021)
This study aims to determine the relationship between environmental performance and environmental disclosure on real earnings management in non-financial companies listed on the Indonesia Stock Exchange in 2017-2019. Using multiple linear regression with quantitative methods and secondary data on 27 companies. Researchers detect real earnings management with Roychowdhury (2006) model, environmental performance with PROPER and environmental disclosure with GRI Standards and GRI G4. The results found are environmental performance has a negative and significant effect on real earnings management on abnormal DISEXP. However, environmental performance has no significant effect on real earnings management through abnormal CFO and abnormal PROD. Furthermore, environmental disclosure has a positive effect on earnings management with abnormal PROD and negative effect on abnormal DISEXP. On the other hand, environmental disclosure has no significant effect on real earnings management through abnormal CFO. Roychowdhury (2006) real earnings management proxy has not been able to reach financial companies on the uniqueness of their financial statements. So that further research is expected to be able to cover financial companies on the IDX.